Transcriptomic analysis of plasmid and plasmid-related chromosomal ORFs in C. trachomatis strains with different cell-appetence - Ferreira, R. (2012)
Despite the undergoing chromosomal size-reduction of Chlamydia trachomatis, almost all strains maintain the conserved 7,5kb plasmid. It has been recently considered a virulence factor, as plasmid-bearing strains evidenced a higher ability to successfully colonize epithelial cells and sustain infection than plasmidless strains. However, the biological role of the eight plasmid ORFs remains poorly characterized. Thus, we aim to correlate the relative expression of each plasmid ORFs with the number of plasmids per genome as well as with the relative expression of chromosomal genes that seem to be regulated by the plasmid, during the whole Chlamydia developmental cycle. Both the transcriptomic analysis of all the selected ORFs and the determination of the plasmid copy number were performed by qPCR in prototype and currently circulating strains with distinct cell-appetence and ecological success, throughout Chlamydia developmental cycle. So far, our results indicate: 1) huge differences (up to 100-fold) in the expression levels between plasmid ORFs; 2) for the same ORF, different expression levels and profiles among strains; 3) variation in the number of plasmids per genome during the infectious cycle; 4) the higher expression level of the plasmid ORFs do not seem to correlate with a higher number of plasmids per genome. These results, together with our ongoing transcriptomic survey of the plasmid-related chromosomal genes, will contribute to shed some light on the molecular function of the plasmid ORFs in chlamydial biology.